THE CONTRIBUTION OF BODY MASS INDEX TO SOME OFFENSIVE SKILLS FOR PLAYERS IN SPECIALIZED FOOTBALL SCHOOLS AGED (14-16) YEARS - Wisam Hameed AbdulRidha; Mustafa AbdulZahra Abbood (Galaxy International Interdisciplinary Research Journal, 2024)
The research aimed to identify the percentage of body mass index contribution to some basic football skills for the ages of (14-16) years, while the research fields included the human field with football players aged (14-16) years, and determine the time range for the period from (13/3/2023) until (25/6/2023).